MiR130b from Schlafen4+ MDSCs stimulates epithelial proliferation and correlates with preneoplastic changes prior to gastric cancer. Issue 10 (24th January 2020) - Ding, Lin; Li, Qian; Chakrabarti, Jayati; Munoz, Andres; Faure-Kumar, Emmanuelle; Ocadiz-Ruiz, Ramon; Razumilava, Nataliya; Zhang, Guiying; Hayes, Michael H; Sontz, Ricky A; Mendoza, Zoe Elena; Mahurkar, Swapna; et al.
Abstract : The myeloid differentiation factor Schlafen4 (Slfn4) marks a subset of myeloid-derived suppressor cells (MDSCs) in the stomach during Helicobacter -induced spasmolytic polypeptide-expressing metaplasia (SPEM). Objective: To identify the gene products expressed by Slfn4 + -MDSCs and to determine how they promote SPEM. Design: We performed transcriptome analyses for both coding genes (mRNA by RNA-Seq) and non-coding genes (microRNAs using NanoString nCounter) using flow-sorted SLFN4 + and SLFN4 – cells from Helicobacter -infected mice exhibiting metaplasia at 6 months postinfection. Thioglycollate-elicited myeloid cells from the peritoneum were cultured and treated with IFNα to induce the T cell suppressor phenotype, expression of MIR130b and SLFN4. MIR130b expression in human gastric tissue including gastric cancer and patient sera was determined by qPCR and in situ hybridisation. Knockdown of MiR130b in vivo in Helicobacter -infected mice was performed using Invivofectamine. Organoids from primary gastric cancers were used to generate xenografts. ChIP assay and Western blots were performed to demonstrate NFκb p65 activation by MIR130b. Results: MicroRNA analysis identified an increase in MiR130b in gastric SLFN4 + cells. Moreover, MIR130b colocalised with SLFN12L, a human homologue of SLFN4, in gastric cancers. MiR130b was required for the T-cell suppressor phenotype exhibited by the SLFN4 + cells and promoted Helicobacter- induced metaplasia. Treating gastric organoids with the MIR130b mimic induced epithelial cell proliferation and promoted xenograft tumour growth. Conclusion: Taken together, MiR130b plays an essential role in MDSC function and supports metaplastic transformation.